Faktor Penentu Jumlah Anak Ideal Di Kecamatan Kuta - Ni Putu Lingkan Yashati; Ni Nyoman Yuliarmi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Ideal number of children is the number of children desired by couple of childbearing age who are able to be cared for and given a decent life. The higher the responsibility for the child's value, the higher the encouragement to plan the ideal number of children. This study aims to analyze the views of couples of childbearing age in determining the ideal number of children in Kuta District both simultaneously and partially. The data in this study uses primary data obtained from interviews with 98 respondents who were used as research samples and secondary data in this study, namely data obtained from the Central Statistics Agency in Kuta District totaling 6.427 people. The results of the study show that based on data on economic conditions, cost of living, education level and socio-cultural level have a simultaneous effect on the ideal number of children in Kuta District. Economic conditions partially have a positive and significant effect on the number of ideal children in Kuta District. The cost of living, education level and socio-cultural level partially have a negative and significant effect on the ideal number of children in Kuta District. The sociocultural variable acts as a moderating variable that weakens the influence of education level on the ideal number of children in Kuta District. The results of this study provide implications for the importance of integration between education and local socio-cultural values in making rational decisions about the number of children.